Effects of multi-stage dehumidified-air drying on the polyphenol content of Hydrocotyle bonariensis - Go, S. K.; Chia, S. L.; Tan, C. P.; Chong, Gun Hean (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Traditional drying methods involve high temperatures that degrade heat-sensitive compounds. Dehumidified-air drying, an alternative to traditional drying methods, is suitable for heat-sensitive compounds; however, it consumes a large amount of energy and is comparatively expensive. In this study, a multi-chamber dehumidified-air dryer was designed to dry Hydrocotyle bonariensis, and the retention of the polyphenol content of Hydrocotyle bonariensis under various drying conditions was examined. Multi-chamber dehumidified-air drying involves two chambers; each chamber was operated at temperatures of 30, 40, and 50°C with air volumetric flow rates of 30 and 50 L/min. The results indicated that the highest retention of total phenolic content and total flavonoid content, 24.67 mg of GAE/g dry weight (DW) and 2.204 mg of catechin/g DW, respectively, was obtained at 50°C with a 50 L/min air flow rate in the first drying chamber. Multi-stage dehumidified-air dryers have the potential to dry heat-sensitive products with reduced energy consumption.